COLLAGE 360: A Model of Person-Centered Care to Promote Health Among Older Adults - Elizabeth, P. Howard; Robert, Schreiber; Aline, Russotto; Susan, Flashner-Fineman (Journal of Aging Research And Healthcare, 2016)
This article describes COLLAGE 360, a person‑centered care model for older adults that integrates comprehensive assessment, goal‑setting, and coordinated community services. The approach seeks to promote health and function while reducing fragmentation across medical and social supports. Early implementation experience outlines feasibility and pathways to measure outcomes and scale within aging networks.
Keywords: person-centered care; wellness coaching; health promotion interRAI comprehensive assessment.